Cerebral stroke prevention programs - Shtefan, Liudmyla Vladimirovna; Mishchenko, Marina Mikhailovna; Shevchenko, Alexander Sergeevich; Mishchenko, Alexander Nikolaevich (Barca Academy Publishing, 2020)
Cerebral strokes are the second most common cause of premature death in the world after coronary (ischemic) heart disease. A significant part of the risk factors for acute cerebrovascular accidents is - manageable‖, so a significant portion of stroke deaths is preventable. For those experiencing transient ischemic attacks and stroke victims, avoiding these risk factors is equally important. The programs of primary, secondary and tertiary prevention of strokes are implemented by medical institutions, medical and social non-governmental organizations, and educational institutions. The prevention of cardiovascular diseases can be included in continuing education programs, briefings and structured cases on the formation of a healthy lifestyle.
Keywords: cardiovascular diseases; cerebral stroke; risk factors; stroke prevention; disability; Social Pedagogy; Health Pedagogy; valeological competence; healthy lifestyle; case study method; production briefings; Post-Stroke Patients School